2015
DOI: 10.1155/2015/363458
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Apolipoprotein E Gene Polymorphism and Severity of Coronary Artery Disease in Acute Myocardial Infarction

Abstract: Apolipoprotein E (ApoE) is a plasma protein and associated with cholesterol transport system. In several studies, the relationship between ApoE gene polymorphism and severity of coronary artery disease (CAD) has been shown. However, the relationship between ApoE gene polymorphism and severity of CAD in patients with acute myocardial infarction (MI) has not been well known. The aim of this study is to investigate the relation between ApoE polymorphism and severity of CAD in patients with acute MI by using the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
3
14
0
1
Order By: Relevance
“…This result is consistent with previous studies [5,6,13]. The study team of Dr. Zülküf Karahan [5] aimed to investigate the relationship between ApoE gene polymorphism and severity of CAD in patients with acute MI. They found that both the levels of LDL cholesterol and TC were observed to be higher in the ApoE34 genotype than in the other genotypes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with previous studies [5,6,13]. The study team of Dr. Zülküf Karahan [5] aimed to investigate the relationship between ApoE gene polymorphism and severity of CAD in patients with acute MI. They found that both the levels of LDL cholesterol and TC were observed to be higher in the ApoE34 genotype than in the other genotypes.…”
Section: Discussionsupporting
confidence: 91%
“…They found that both the levels of LDL cholesterol and TC were observed to be higher in the ApoE34 genotype than in the other genotypes. Many studies concluded that the ApoE4 allele is associated with higher serum levels of TC, LDL cholesterol, and VLDL cholesterol, and higher risk of CAD [5,6,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tais resultados corroboram um estudo que analisou a associação entre o genótipo da ApoE e DCVs, verificando que a gravidade das lesões coronarianas em idosos não apresentou associação com o alelo ɛ4 (13) . Outros estudos realizados com indivíduos idosos, verificando a associação do alelo ɛ4 com complicações cardiovasculares encontraram resultados controversos (16)(17) . Nessa mesma linha, não se observou associação entre os valores alterados de lipídios, glicemia, variáveis antropométricas e pressão arterial entre os diferentes genótipos da ApoE em uma população de idosos, verificando apenas aumento de HDL-colesterol no grupo de idosos considerados fisicamente ativos e portadores do alelo ɛ4.…”
Section: Discussionunclassified
“…1 Many risk factors contribute to the pathogenesis of CAD, such as smoking, diabetes, hypertension, hypercholesterolemia, obesity, physical inactivity and stress. 2 Although many patients with CAD share similar risk factors, it is not clear why some individuals are more susceptible to these environmental determinants than others with the same risk factors, pointing to a complex interaction of both environmental and genetic factors.…”
Section: Introductionmentioning
confidence: 99%